2022
DOI: 10.1371/journal.pone.0269647
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-mediated effects on airway innate immunity in vitro

Abstract: Introduction Vitamin D supplementation has been suggested to enhance immunity during respiratory infection season. We tested the effect of active vitamin D (calcitriol) supplementation on key airway innate immune mechanisms in vitro. Methods Primary human airway epithelial cells (hAECs) grown at the air liquid interface were supplemented with 10−7 M calcitriol for 24 hours (or a time course) and their antimicrobial airway surface liquid (ASL) was tested for pH, viscoscity, and antibacterial and antiviral pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…They suggested that calcitriol acts by modulating the vitamin D receptor pathway to increase the expression of cathelicidin. It has effects on several innate immune mechanisms in the airway (Stapleton et al 2022 ). The conflicting effects of calcitriol may be due to differences in vitamin D metabolism and the dose of calcitriol given to mice may have been too low to maintain adequate levels.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that calcitriol acts by modulating the vitamin D receptor pathway to increase the expression of cathelicidin. It has effects on several innate immune mechanisms in the airway (Stapleton et al 2022 ). The conflicting effects of calcitriol may be due to differences in vitamin D metabolism and the dose of calcitriol given to mice may have been too low to maintain adequate levels.…”
Section: Resultsmentioning
confidence: 99%
“…Levels of vitamin D in infancy did not predict TB disease (hazard ratio = 0.8, 95% CI, 0.4–1.6); however, severe vitamin D deficiency (<30 nmol/l) was associated with TB infection in children 2 years or less of age (aOR=1.9, 95% CI, 1.2–3.2) [85 ▪▪ ]. Mechanistically, vitamin D upregulates the expression of antimicrobial peptides, such as cathelicidin, a protein expressed by leukocytes and epithelial cells that disrupts the integrity of the bacterial cell membrane; thus, vitamin D has been proposed as a possible intervention to prevent bacterial infection [86,87 ▪ ]. In a large clinical trial, 8851 Mongolian children, 96% of whom were vitamin D deficient, were randomized to receive weekly oral vitamin D supplementation or placebo, and tested for TB infection (QuantiFERON-TB Gold) after a 3-year period [88].…”
Section: Clinicalmentioning
confidence: 99%